An Experimental Approach to Optimizing Automated Hybrid Ventilation in Complex Buildings - Taylor, Nathan (My University, 2012)
Complex buildings such as hospitals and laboratories require intensive ventilation and cooling loads in order to meet operational demands. One way to reduce energy use while meeting these demanding requirements in complex buildings is the incorporation of hybrid ventilation in areas that do not require high and continuous loads such as public spaces. This research establishes an experimental approach to test and analyze various hybrid ventilation strategies in an occupied, complex building utilizing hybrid ventilation in public spaces. To optimize the use of hybrid ventilation, this research focuses on tracking three performance criteria: energy savings, occupant comfort and indoor-air quality. The framework establishes a variety of hybrid ventilation strategies to test, and outlines how to analyze results graphically and through linear regression modeling. This experimental approach is illustrated through a case study example of a laboratory building located in Madison - Wisconsin, where the selection of the ideal hybrid ventilation strategy for the public space studied resulted in 56 percent average savings in ventilation and cooling load when HV is in use, and established a potential to use hybrid ventilation for 28 percent of the 111 day cooling season (20 percent savings in mechanical cooling over the summer).
Keywords: experimental method; natural ventilation; complex buildings; Energy savings; Hybrid ventilation